Mentor-mentee program with Medical Students: A successful program with ethical considerations - Tin, Tin Thein; Tun Aung; Aye Aye Wynn; Win Win Than; Mie, Mie Sein; Nang Khin Mya; Fairrul Masnah @ Kadir (Penerbit UMS, 2021)
Background: Mentoring is the relationship of a guide or a teacher with another person/student augmenting his/her carrier growth, knowledge, skills, and experiences implemented by caring, sharing and helping hands. The aim of this paper is to highlight the mentoring, type of mentoring, how important of matching and consideration of ethical issue in mentoring program. Not missing these significant points, mentoring program could be successful in universities including medical faculty. Methods: The SMART principles of specific, measurable, attainable, relevant, and time-bound are essential to structure the matching between mentor and mentee. The rule of etiquette and ethical issues are crucial and beneficial for mentor-mentee relationship. Clinical mentoring programs help to develop students’ clinical skills and can increase interest in under-subscribed specialties. Positive mentoring plays a part in reversing the decline of academic medicine, by sparking interest through early research experiences. Results: There is the short term goal which is to introduce an immediate support network for incoming students and the long term goal is to cultivate a mentoring culture to engage all strata of medical students and every faculty member. Medical students expressed that mentoring program is to provide counselling, develop professionalism, increase students' interest in research, and support them in their personal growth. Conclusion: The goal of mentorship is to provide additional support to student or mentee by steering of the academic needs or social prerequisites to accelerate the personal and professional development of mentee with advice, guide and feed backs from the mentor.